Romantics and Renegades - Mahoney, C. author. aut Link
X, 266 p.
Keywords: Romantics and Renegades examines the abiding crux of romantic criticism: the political apostasies of the Lake poets (Wordsworth, Coleridge, and Southey) as they renounced the revolutionary Jacobinism of their youth in the 1790s in order to claim the high ground of Regency Toryism in the 1810s. Central to this scandal is the figure of William Hazlitt, the literary critic who policed their betrayals in his vigilant exposure of their political and poetical inconsistencies. Mahoney's analysis provides new insight into this abiding critical riddle through close historical and figural readings of the rhetoric of romantic apostasy.